2015
DOI: 10.7554/elife.05560
|View full text |Cite
|
Sign up to set email alerts
|

The prenyltransferase UBIAD1 is the target of geranylgeraniol in degradation of HMG CoA reductase

Abstract: Schnyder corneal dystrophy (SCD) is an autosomal dominant disorder in humans characterized by abnormal accumulation of cholesterol in the cornea. SCD-associated mutations have been identified in the gene encoding UBIAD1, a prenyltransferase that synthesizes vitamin K2. Here, we show that sterols stimulate binding of UBIAD1 to the cholesterol biosynthetic enzyme HMG CoA reductase, which is subject to sterol-accelerated, endoplasmic reticulum (ER)-associated degradation augmented by the nonsterol isoprenoid gera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 64 publications
(105 reference statements)
8
86
1
Order By: Relevance
“…In the course of our studies, we discovered that GGpp also stimulates translocation of UBIAD1 from the ER to the Golgi (12). SCD-associated UBIAD1 (N102S) and (G177R) are refractory to this GGpp-induced Golgi transport and localize to the ER.…”
Section: Cell Culturementioning
confidence: 97%
See 4 more Smart Citations
“…In the course of our studies, we discovered that GGpp also stimulates translocation of UBIAD1 from the ER to the Golgi (12). SCD-associated UBIAD1 (N102S) and (G177R) are refractory to this GGpp-induced Golgi transport and localize to the ER.…”
Section: Cell Culturementioning
confidence: 97%
“…We postulate that GGOH becomes converted to GGpp, which augments reductase ERAD by enhancing its membrane extraction (21). Recently, we found that sterols also cause reductase to bind to UBIAD1 (12). GGpp triggers release of UBIAD1 from reductase, allowing for its maximal ERAD.…”
Section: Cell Culturementioning
confidence: 99%
See 3 more Smart Citations